Connectivity between Asia and Europe: Implications for infrastructure convergence between the two regions - Naoyuki Yoshino; Monzur Hossain; Farhad Taghizadeh-Hesary (Asian Development Bank Institute (ADBI), 2020)
While discussing the enhancement of the connectivity between Europe and Asia, this policy paper explores a new area of cooperation, which is the use of European long-term investment funds in Asia's infrastructure. We argue that, if Asian countries agree to offer 50% of their spillover revenue to infrastructure investors from Europe, it will increase the rate of return of long-term investment funds, such as pension and insurance funds. This will create a win-win situation for both Asia and Europe, because investment in infrastructure will enhance various spillover benefits and increase the savings in these countries, which will ultimately enhance the economic growth in the Asian countries. On the other hand, idle European funds will generate higher returns from infrastructure investments in Asia, which will also be beneficial for European countries. This approach will reduce the divergence in infrastructure between the two regions and encourage regional connectivity, such as the People's Republic of China's Belt and Road Initiative. With some empirical evidence, this paper also highlights the methods of spillover revenue collection and approaches to share the revenues. It is important for Asian countries to review the approaches and develop some institutional mechanisms to allow private investors in infrastructure. Moreover, Asian and European leaders, for example in the Asia-Europe Meeting, might devise appropriate methods that would allow European long-term investors to invest in Asian infrastructure needs.
Keywords: O22; O23; O24; F36; F37; 330; financial connectivity; infrastructure investments; spillover tax revenue; pension and insurance funds; Europe; Asia